Pendidikan Kesehatan pada Remaja Putri tentang Kesehatan Reproduksi di SMP Pertiwi 1 Kota Jambi - Hesty, Hesty; Maimaznah, Maimaznah; Hidayat, Muhammad (Universitas Baiturrahim, 2024)
Reproductive health is an important aspect in the lives of individuals and society. According to WHO, reproductive health includes efforts to maintain and improve the physical, mental and social well-being of individuals in all stages of life related to the reproductive system. Factors that influence reproductive health include social, economic, cultural and environmental. Junior High School (SMP) is a place of education where the average student is a teenager and of course needs to be equipped with knowledge and motivation related to reproductive health in order to avoid various problems related to reproduction, considering that teenagers are sometimes negligent and lack attention to their reproductive health, p. Even this can be seen in the initial study, information from student affairs teachers regarding reproductive health issues has not been specifically provided, nor has the Putri Ayu Community Health Center, which oversees it and is part of its working area, since 2 years ago only provided blood supplement tablets for teenagers, whereas for Health education related to reproduction for adolescents has not been provided. This service activity was carried out at Pertiwi 1 Middle School, Jambi City, in the form of group education, for ± 60 minutes in the classroom. The method of implementing activities is pre-test and post-test through questionnaires, lectures and discussions. This activity aims to increase young women's knowledge about reproductive health. The target of this community service activity is 7th grade teenage girls (20 female students) using leaflet media. The results of the evaluation during the educational process showed that participants seemed enthusiastic about the counseling material, participants listened to the counseling carefully and participants asked questions regarding material that was unclear. The results of the analysis of pre-test and post-test questionnaires on 20 participants showed that there was an increase in knowledge from before the educational activity, namely 47% and after the educational activity to 87%.